1985
DOI: 10.1002/prep.19850100604
|View full text |Cite
|
Sign up to set email alerts
|

On the adhesion between Hydroxyl‐Terminated Polybutadiene Fuel‐Binder and Ammonium Perchlorate. Performance of bonding agents

Abstract: and T. FukudaNippon Oil and Fats Co., Taketoyo-machi, Chita-gun, Aichi-Pref. (Japan) h e r die Haftung zwischen hydroxy-terminierten Polybutadien-Treibstoffbindern und Ammoniumperchlorat. Wirksamkeit der Haftvermittler Eine einfache Methode zur Berechnung der Adhasionskraft zwischen Feststoffoxidator und polymerem Treibstoffbinder wird vorgefuhrt. Zur Illustration werden hydroxy-terminierte Polybutadienstabchen, die unterschiedliche Haftvermittler enthalten, auf Ammoniumperchlorat-Einkristalle aufgebracht . Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…Since it has been illustrated in figures 3a and 3b that the considered energetic fillers have very similar shapes, the difference of matrix/filler adhesion is probably responsible for the observed changes on the composite behaviors. This assumption is also supported by previous works on the effect of matrix/filler adhesion on the mechanical behavior of particulates composites [5] and solid propellants [11,14] arguing that the highest stress levels experienced by ammonium perchlorate filled composites compared to HMX filled composites are due to a better matrix/filler adhesion in the former case. Figure 5c shows the mechanical behavior of matrix B filled with HMX particles.…”
Section: Polyacrylate and Glass Beadssupporting
confidence: 76%
See 1 more Smart Citation
“…Since it has been illustrated in figures 3a and 3b that the considered energetic fillers have very similar shapes, the difference of matrix/filler adhesion is probably responsible for the observed changes on the composite behaviors. This assumption is also supported by previous works on the effect of matrix/filler adhesion on the mechanical behavior of particulates composites [5] and solid propellants [11,14] arguing that the highest stress levels experienced by ammonium perchlorate filled composites compared to HMX filled composites are due to a better matrix/filler adhesion in the former case. Figure 5c shows the mechanical behavior of matrix B filled with HMX particles.…”
Section: Polyacrylate and Glass Beadssupporting
confidence: 76%
“…The high volume fraction of particles [31], the nonlinear hyperelastic behavior of the elastomer matrix, the particle size [5,10,14,31] and the matrix/particles adhesion [11,14,15] give very specific tensile properties to solid propellants compared to other class of filled polymer matrix. For instance, it has been showed that damage by filler/matrix debonding has a very significant effect on the mechanical behavior of solid propellants [20,3,1,26] that is not fully understood despite recent studies [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This difference could stem from the fact that on the one hand, in the calculations, the presence of ab onding agent was solely accounted for throught he introduction of an interphase but no modification of the filler/matrix properties was implemented. Whereas, on the other hand, bonding agent are designed to reinforce the matrix/filler bond [41].Y et, it has been demonstrated [ 8,28] that ac hange of the critical strength or of the debonding energy of the cohesive zone, which both representamodification of the interface,c an produce sucha nincrease in the stressa tbreak. stiffer the interphase, the stiffer the composite and the larger its stress at failure.…”
Section: Effect Of the Interphase Thicknessmentioning
confidence: 99%
“…São compostos com funções orgânicas de amidas aziridínicas hidroxiladas ou não, aminas di ou trihidroxiladas, aminas cianohidroxiladas, amidas di hidroxiladas entre outras. Os agentes de ligação atuam sobre os sólidos, perclorato de amônio e alumínio, através de ligações verdadeiras e/ou por ligações secundárias, adsorção ou atração de cargas 21,23 . superfície da partícula para formar uma camada firme e resistente sobre os mesmos, envolvendo-os completamente permitindo que se liguem à matriz polimérica [25][26][27] .…”
Section: A Importância Do Agente De Ligaçãounclassified